Educação profissional no Brasil do século XXI políticas, críticas e perspectivas - vol. 2 - Filho, Domingos Leite Lima (Editora Oficina Universitária, 2023)
Faced with the less than encouraging scenario of contemporary Brazil, we dare to hand over the collection Professional Education in Brazil in the 21st Century: Policies, Criticisms and Perspectives vol. 2. The present volume does not differ essentially from the first, but being a second publication, it indicates the social necessity of its birth. Bearing in mind that only one volume was not enough to cover the whole range of issues surrounding professional education in the context of the structural crisis of capital. of the working class is elected, in a commonplace way, as the apple of an eye for the solution of the problems of capitalist destructive production.